Analysis of Business Model Development in Culinary Businesses Using a Cost-Restricted Business Model Canvas for PNM Mekaar Customers, Banjarnegara Branch - Puji Santoso; A. Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to map, evaluate and improve the business model of the culinary business of PNM Mekaar Banjarnegara Branch customers. This study uses qualitative methods with data collection tools through Focus Group Discussions (FGD) and in-depth interviews to obtain information and analyze business models. The research subjects were the customers of PNM Mekaar Banjarnegara Branch. The results of the study show that culinary business actors carried out by customers of PNM Mekaar Banjarnegara Branch have not fully used the Business Model Canvas. The nine elements of the Business Model Canvas are added for improvement as a future business development effort. Furthermore, the results of the SWOT analysis also obtained 10 strategies that can be used as alternatives for future business development